Factors Causing Anxiety of Pregnant Women in Delivery - Rizky Vaira; Merlin Karinda; Rabia Wahdah (PT Inovasi Pratama Internasional, 2023)
A woman will experience anxiety in facing labor, especially in the first pregnancy. This study aims to determine the factors that cause anxiety in pregnant women in facing labor. This type of research method with a cross-sectional study. The sample in this study were all pregnant women who made a pregnancy check-up visit to the Independent Midwife Practice (PMB) in the Banjarmasin City Region, totaling 80 people. Sampling technique with Accidental Sampling. The research instrument used a questionnaire consisting of the age of the pregnant woman, the number of children born, the gestational age and the husband's role. Data analysis using a computer program. The results showed that pregnant women experienced more anxiety (66.3%), compared to pregnant women who did not experience anxiety (33, 8%). There is a relationship between the age of pregnant women with a p-value of 0.033 (<0.05), the number of children with a p-value of 0.039 (<0.05), the gestational age of the p-value of 0.020 (<0.05) and the role of the husband p-value 0.039 (<0.05) with anxiety of pregnant women in facing labor. Pregnant women experience anxiety in facing childbirth and need a husband as a companion. Midwives need to educate husbands so that they always accompany their wives in the process of pregnancy and delivery.